2017
DOI: 10.20944/preprints201707.0071.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perception of Tourism Impact and Support Tourism Development in Malaysia

Abstract: 1) Background: Tourism is one of the prominent industry that has a capability to generate handsome income for developed as well as developing countries. However, the study to investigate specifically the perception of local residents towards tourism is still lacking. The perception of the locals is important since it could determine the extent of their support for tourism development. Plus, previous research found that male residents are more support better towards the tourism development. Thus, this factor is… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Dwyer et al (2009) Previous studies confirm that economic tourism impacts are perceived by residents as a mean to generate employment, improve local economy and increase investments (Pham & Kayat, 2011). On the other hand, there is a dark side of it, portrayed in the increase in the cost of living and the feeling of injustice regarding the distribution of profits generated by tourism (Afthanorhan, Awang & Fazella, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Dwyer et al (2009) Previous studies confirm that economic tourism impacts are perceived by residents as a mean to generate employment, improve local economy and increase investments (Pham & Kayat, 2011). On the other hand, there is a dark side of it, portrayed in the increase in the cost of living and the feeling of injustice regarding the distribution of profits generated by tourism (Afthanorhan, Awang & Fazella, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A planned and well managed corporate image is the most promising marketing strategy in order to attract current consumers (Ghazali et al, 2017). Nguyen and Leblanc (2001) and Afthanorhan et al (2017) found that corporate image is related to the physical and behavioural attributes of the firm such as business name, architecture, services and to the impression of quality communicated by each person interacting with the firm's clients. They also defined that corporate image is associated with positively with customer loyalty in three sectors which is telecommunication, retailing and education.…”
Section: Corporate Imagementioning
confidence: 99%
“…The results of bootstrapping procedure in testing the mediator customer satisfaction Here, the study used bootstrapping procedure to confirm the indirect effect and direct effect between the constructs as recommended by Afthanorhan et al (2017Afthanorhan et al ( , 2018Afthanorhan et al ( , 2018) and Bakar et al (2008). Table 6 shows the beta estimate of both the indirect effect and the direct effects of Hospital Image and Patients' Satisfaction (β) = 0.121 and 0.086 respectively.…”
Section: Tablementioning
confidence: 99%
“…The author proposed a conceptual framework that highlighted the need to theoretical interventions to behavior based safety performance conceptual framework with emphasis assigned to climate factors in enhancing behavior based safety performance.This current study provides conceptual framework based on integrating Theory of Planned Behavior (TPB) and Social Exchange Theory (SET; Afthanorhan, Awang, & Fazella, 2017;Afthanorhan et al, 2018). Both theoretical rationale and empirical data indicate the presence of signifi cant variation among employees in the organization.…”
Section: Theoretical Argumentmentioning
confidence: 97%